Effects of YSZ and nano-ZrO2 contents on the properties of Ti2448-ZrO2 biomedical composites fabricated by SPS. Issue 11 (1st August 2018) - Zhang, Bowen; Ma, Beiyue; Zhang, Xinyue; Zhu, Qiang; Ren, Xinming; Zhang, Yaran; Qu, Xuanhui; Yu, Jianbo; Yu, Jingkun
Abstract: This study aims to evaluate the effects of ZrO2 types including YSZ and nano-ZrO2 as well as their contents on the phase compositions, macrostructures, microstructures, physical properties, mechanical properties and biocompatibility of Ti2448-ZrO2 composites fabricated by spark plasma sintering (SPS). The mechanical properties such as hardness and compressive yield strength of the composites have been systematically investigated. The experimental results demonstrate that the hardness and compressive yield strength of the composites all dramatically increased with increasing the content of YSZ and nano-ZrO2 . Meanwhile the nano-ZrO2 could be beneficial to the uniformity of microstructure and improvement in mechanical strength of the composites. The biocompatibility of the composites containing nano-ZrO2 was found to possess better corrosion resistance. In conclusion, Ti2448-ZrO2 composites are potentially useful in biomedical applications with their mechanical and biological properties being evaluated in this work.